Supply Policy Implication of Public Cultural Services in Urban Communities from The Perspective of Overall Governance: A Case Study Take Zhanjiang Community - Weichan, Deng; Niyomyaht, Satit; Kalyanamitra, Kamolporn; Siriphornwut, Nattawat (International Journal of Multidisciplinary in Management and Tourism, 2024)
Urban public service is an important issue for government policy that should be understood by the public and should be coordinated with regulatory agencies and decentralized between different levels of government. Take care of public community cultural services because it matches the theory of holistic governance. This article aimed to 1) study the information of the people using the public cultural services of Zhanjing community and 2) study satisfaction in using public cultural services of communities in Zhanjing City. The study used representatives of three communities in Chikan District, Xiashan District, and Mazhang District from the four administrative regions of Zhanjiang Province, selected as R&D centers. A sample size of 900 people was used, with 884 questionnaires returned, the data collection tool is a questionnaire. In this study, the researchers used statistical methods to conduct basic statistics on the data, such as percentage, mean, standard deviation, and one-way analysis of varied. The research results were found as follows; 1. The respondents' personal information found that most of them were 586 females, and 298 males, with an average age of 21-30 years, most of them undergraduate education, 364 people, and most were students. 2. Most respondents are satisfied with community public cultural facilities and have a good attitude towards government public cultural facilities.